Relative Bradycardia in Critically Ill Patients with Novel Coronavirus 19: A Case Series - Qingpeng Li; Liyun Luo; Wenyi Tang; Jian Chen (Cardiology Discovery)
Severe coronavirus 2019 (COVID-19) infection is associated with myocardial injury and arrhythmia. Bradycardia is a newly recognized consequence of COVID-19. Relative bradycardia and its effects in 4 critically ill patients with COVID-19 was described in this case series. The 4 cases showed the same clinical phenomenon: sinus bradycardia without a compensatory increase in heart rate in response to elevation of body temperature. Typically, heart rate decreases as body temperature rises. The 4 patients were all men with an average age of 67 years. Patient 1 was a 78-year-old man with no major medical history who died from COVID-19 pneumonia. The other 3 patients recovered.